The Web-based Application of Small and Medium Enterprises (SMEs) Product Distribution Management with Content Management System Shopify Integration in Netasia Singapore - Arsha Raulnadi Trikusuma; Noora Qotrun Nada; Mega Novita (Advance Sustainable Science, Engineering and Technology (ASSET), 2022)
Netasia is a brand activation of the company named Golden Style Management Lte. Ptd. in Singapore which acts as a local partner and distributor for Small and Medium Enterprises (SMEs) from Indonesia. Netasia utilizes Content Management System (CMS) named Shopify to reach end-users. But currently, they do not have a platform for managing product distribution from preorders to vendors until distribution to stores. This research was conducted to develop a web-based application of SMEs product distribution management with CMS Shopify integration in Netasia Singapore. This research was conducted using Research and Development (RnD) method for research approaches and prototyping method for software development. The prototyping method often involves communication between developers and the company as application users, so that the application undergoes several changes. As the result of this research, the application has been successfully integrated with the data from the company's CMS Shopify through the API using cURL. The application was tested with several testing methods such as 1) black-box testing with 100% succeed percentage so the application is proper to use, 2) white-box testing with cyclomatic complexity of 4 and 100% succeed percentage for value test so the application passed the software engineering criteria, 3) User Acceptance Testing (UAT) with 94% average percentage so the application meets user expectations, and 4) browser application compatibility testing with the results that the application is compatible with all of the browser applications specified in this research for the menus function aspect, and less compatible with the Internet Explorer browser for the user interface aspect.